Extraction the Dayak Onion (Eleutherine sp): Scientific Based Herbal Medicine (OHT) Production Protocol - Hery Poerwosusanta; Zairin Noor; Karyono Mintaroem; Edi Widjajanto; Mulyohadi Ali (Berkala Kedokteran, 2019)
Abstract: Indonesia has the second largest tropical forest and the richest in flora biodiversity in the world. Based on the Basic Health Research 2010, 59.29% of Indonesian had consumed herbal medicine, noted that Indonesian had consumed herb since the VIII century. Dayak onion (Eleutherine sp) widely used as traditional medicine, as a bahimang /wound healing agent. Dayak onion is not reassured as a medical treatment and lacked scientific evidence. Until 2018, thousands of herbs consumed by Indonesian, only 85 ingredients clinically tested. Sixty-four herbs have been pre-clinically tested and designated as Scientific based Herbal Medicines/Obat Herbal Terstandar (OHT) and 21 herbs have been tested clinically and determined as Phytopharmaca by the Badan Pengawasan Obat dan Makanan Republik Indonesia (BPOM-RI). Based on the data, the Dayak onion appointed as a Scientific based Herbal medicine (OHT) based on pre-clinical and phase 0 clinical research.  Potential and promising for the treatment of metabolic, degenerative, catastrophic, neoplasmic, genetic and infectious diseases, Dayak onions can be developed into phytopharmaca in the future. The study aim is to make guidelines for the standardized herbal medicines development according to the rules and regulations. Keywords: Dayak Onion, Eleutherine sp, Scientific based Herbal Medicines, Phytopharmaca, Pre Clinic and Clinical Trials phases